Kecemasan Orang Tua Ketika Anak Berinteraksi Sosial di Masa Pandemi Covid-19 - Padila Padila; Dhea Septeah Ningrum; Juli Andri; Andry Sartika; Muhammad Bagus Andrianto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to describe the level of parental anxiety when children interact socially during the Covid-19 pandemic in the work area of the Beringin Raya Public Health Center, Bengkulu City. The research method used in this study is a descriptive method with a quantitative approach. The results showed that the description of the level of anxiety of parents when their children interacted socially during the COVID-19 pandemic from 45 respondents, the category of not being anxious was five respondents (11.1%), mild anxiety was 37 respondents (82.2%), and moderate anxiety was three respondents. (6.7%). In conclusion, the description of the level of anxiety of parents when children interact socially during the COVID-19 pandemic in the work area of the Beringin Raya Public Health Center in Bengkulu City is mainly classified as mild anxiety. Keywords: Anxiety, Parents, Covid-19 Pandemic